2009
DOI: 10.1111/j.1365-2826.2009.01854.x
|View full text |Cite
|
Sign up to set email alerts
|

A Biological Role for the Gonadotrophin‐Releasing Hormone (GnRH) Metabolite, GnRH‐(1‐5)

Abstract: Gonadotrophin‐releasing hormone (GnRH) was first isolated in the mammal and shown to be the primary regulator of the reproductive system through its initiation of pituitary gonadotrophin release. Subsequent to its discovery, this form of GnRH has been shown to be one of many structural variants found in the brain and peripheral tissues. Accordingly, the original form first discovered and cloned in the mammal is commonly referred to as GnRH‐I. In addition to the complex regulation of GnRH‐I synthesis, release a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 91 publications
(167 reference statements)
0
3
0
Order By: Relevance
“…Although PEP and TOP cooperate in hydrolysis of GnRH, and may function separately or in concert in protection from amyloid toxicity (Arif et al , 2009), each has distinct roles in other physiological processes in the brain as well as peripherally. TOP may act in brain to play a role in lordosis in female rodents (Wu et al , 2009), is implicated in neurotensin inactivation (Ferro et al , 2004), and its central role in bradykinin breakdown may extend to regulation of the cerebral microvasculature (Norman et al , 2001). PEP is thought to contribute to control of the cell cycle, learning, memory, mood, and several neurodegenerative diseases (Männisto et al , 2007; Rossner et al , 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PEP and TOP cooperate in hydrolysis of GnRH, and may function separately or in concert in protection from amyloid toxicity (Arif et al , 2009), each has distinct roles in other physiological processes in the brain as well as peripherally. TOP may act in brain to play a role in lordosis in female rodents (Wu et al , 2009), is implicated in neurotensin inactivation (Ferro et al , 2004), and its central role in bradykinin breakdown may extend to regulation of the cerebral microvasculature (Norman et al , 2001). PEP is thought to contribute to control of the cell cycle, learning, memory, mood, and several neurodegenerative diseases (Männisto et al , 2007; Rossner et al , 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, one of the products of TOP action on GnRH, GnRH1-5, is bioactive in promoting lordosis and in GnRH auto-regulation (reviewed in Roberts et al , 2007; Wu et al , 2009). The involvement of TOP and other neuropeptidases in breakdown of GnRH suggests that these enzymes may be another component of the hypothalamic-pituitary-gonadal HPG axis and therefore candidates for regulation by the end products, steroid hormones.…”
Section: Introductionmentioning
confidence: 99%
“…Thimet oligopeptidase (EC 3.4.24.15; EP24.15, THOP1) was initially identified as a neuropeptide-inactivating enzyme in rat brain homogenates [1,2,3,4]. The majority of well-characterized THOP1 substrates are neuropeptides [5], including bradykinin [6,7], neurotensin [8,9,10], opioid peptides [1,11,12], angiotensin [13], and gonadotrophin-releasing hormone (GnRH) [14,15,16]. Studies have suggested that THOP1 could be secreted or associated to the external surface of the plasma membrane to function as a neuropeptide-degrading enzyme [17,18,19].…”
Section: Introductionmentioning
confidence: 99%